Media Sosial dan Perubahan Standar Kecantikan pada Wanita Jawa: Analisis Seometika Roland Barthes pada Akun TikTok @darasarasvati - Qirrana Amelia Putri; Didi Permadi; Sarwo Edy (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to describe how Javanese women's beauty is represented in the TikTok content of @darasarasvati and to analyze how local cultural symbols are reinterpreted within the context of digital aesthetics using Roland Barthes' semiotic approach. Through the analysis of signs consisting of signifiers and signifieds including denotative, connotative, and mythological meanings this study reveals how local cultural symbols such as kebaya, skin tone, traditional music, and captions are reinterpreted through digital visual aesthetics. The findings show that TikTok functions as a space for identity negotiation, where tradition is blended with global trends in an aesthetic and viral format. The kebaya is no longer seen merely as traditional attire but as a symbol of the modern, elegant woman. Bright skin tones, visual filters, and transition effects also reflect the dominance of global beauty standards over local values. This research concludes that social media is not a neutral platform but a site of ideological production that constructs new myths about the ideal Javanese woman: beautiful, cultured, and modern.